Contributions of phenotypic integration, plasticity and genetic adaptation to adaptive capacity relating to drought in Banksia marginata (Proteaceae) - Oyanoghafo, Osazee O.; Miller, Adam D.; Toomey, Madeline; Ahrens, Collin W.; Tissue, David T.; Rymer, Paul D. (Frontiers in Plant Science, 2023)
The frequency and intensity of drought events are predicted to increase because of climate change, threatening biodiversity and terrestrial ecosystems in many parts of the world. Drought has already led to declines in functionally important tree species, which are documented in dieback events, shifts in species distributions, local extinctions, and compromised ecosystem function. Understanding whether tree species possess the capacity to adapt to future drought conditions is a major conservation challenge. In this study, we assess the capacity of a functionally important plant species from south-eastern Australia (Banksia marginata, Proteaceae) to adapt to water-limited environments. A water-manipulated common garden experiment was used to test for phenotypic plasticity and genetic adaptation in seedlings sourced from seven provenances of contrasting climate-origins (wet and dry). We found evidence of local adaptation relating to plant growth investment strategies (plant height, total leaf area, and specific leaf area), with populations from drier climate-origins showing reduced investment in growth under water-limited conditions but greater growth in well-watered conditions. The results also revealed that environment drives variation in physiological (stomatal conductance, predawn and midday water potential) and structural traits (wood density, leaf dry matter content). Finally, these results indicate that traits are coordinated to optimize conservation of water under water-limited conditions and that phenotypic integration does not constrain phenotypic plasticity. Overall, this study provides evidence for adaptive capacity relating to drought conditions in B. marginata, and a basis for predicting the response to climate change in this functionally important plant species.